Axillary dissection versus no axillary dissection in patients with breast cancer and sentinel-node micrometastases (IBCSG 23-01): 10-year follow-up of a randomised, controlled phase 3 trial. Issue 10 (October 2018) - Galimberti, Viviana; Cole, Bernard F; Viale, Giuseppe; Veronesi, Paolo; Vicini, Elisa; Intra, Mattia; Mazzarol, Giovanni; Massarut, Samuele; Zgajnar, Janez; Taffurelli, Mario; Littlejohn, David; Knauer, Michael; et al.
Summary: Background: We previously reported the 5-year results of the phase 3 IBCSG 23-01 trial comparing disease-free survival in patients with breast cancer with one or more micrometastatic (≤2 mm) sentinel nodes randomly assigned to either axillary dissection or no axillary dissection. The results showed no difference in disease-free survival between the groups and showed non-inferiority of no axillary dissection relative to axillary dissection. The current analysis presents the results of the study after a median follow-up of 9·7 years (IQR 7·8–12·7). Methods: In this multicentre, randomised, controlled, open-label, non-inferiority, phase 3 trial, participants were recruited from 27 hospitals and cancer centres in nine countries. Eligible women could be of any age with clinical, mammographic, ultrasonographic, or pathological diagnosis of breast cancer with largest lesion diameter of 5 cm or smaller, and one or more metastatic sentinel nodes, all of which were 2 mm or smaller and with no extracapsular extension. Patients were randomly assigned (1:1) before surgery (mastectomy or breast-conserving surgery) to no axillary dissection or axillary dissection using permuted blocks generated by a web-based congruence algorithm, with stratification by centre and menopausal status. The protocol-specified primary endpoint was disease-free survival, analysed in the intention-to-treat population (as randomly assigned). Safety was assessed in all randomly assigned patients who received their allocated treatment (as treated). We did a one-sided test for non-inferiority of no axillary dissection by comparing the observed hazard ratios (HRs) for disease-free survival with a margin of 1·25. This 10-year follow-up analysis was not prespecified in the trial's protocol and thus was not adjusted for multiple, sequential testing. This trial is registered withClinicalTrials.gov, numberNCT00072293 . Findings: Between April 1, 2001, and Feb 8, 2010, 6681 patients were screened and 934 randomly assigned to no axillary dissection (n=469) or axillary dissection (n=465). Three patients were ineligible and were excluded from the trial after randomisation. Disease-free survival at 10 years was 76·8% (95% CI 72·5–81·0) in the no axillary dissection group, compared with 74·9% (70·5–79·3) in the axillary dissection group (HR 0·85, 95% CI 0·65–1·11; log-rank p=0·24; p=0·0024 for non-inferiority). Long-term surgical complications included lymphoedema of any grade in 16 (4%) of 453 patients in the no axillary dissection group and 60 (13%) of 447 in the axillary dissection group, sensory neuropathy of any grade in 57 (13%) in the no axillary dissection group versus 85 (19%) in the axillary dissection group, and motor neuropathy of any grade (14 [3%] in the no axillary dissection group vs 40 [9%] in the axillary dissection group). One serious adverse event (postoperative infection and inflamed axilla requiring hospital admission) was attributed to axillary dissection; the event resolved without sequelae. Interpretation: The findings of the IBCSG 23-01 trial after a median follow-up of 9·7 years (IQR 7·8–12·7) corroborate those obtained at 5 years and are consistent with those of the 10-year follow-up analysis of the Z0011 trial. Together, these findings support the current practice of not doing an axillary dissection when the tumour burden in the sentinel nodes is minimal or moderate in patients with early breast cancer. Funding: International Breast Cancer Study Group.